Analysis of 24 years of mesopause region OH rotational temperature observations at Davis, Antarctica. Part 2: Evidence of a quasi-quadrennial oscillation (QQO) in the polar mesosphere - French, W. John R.; Klekociuk, Andrew R.; Mulligan, Frank J. (2020)
Observational evidence of a quasi-quadrennial oscillation (QQO) in the polar mesosphere is presented based on the analysis of 24 years of hydroxyl (OH) nightglow rotational temperatures derived from scanning spectrometer observations above Davis Research Station, Antarctica (68° S, 78° E). After removal of long term trend and solar cycle responses, the residual winter mean temperature variability contains an oscillation over an approximately 3.5–4.5 year cycle with an amplitude of 3–4 K. Here we investigate this QQO feature in the context of the global temperature, pressure, wind and surface fields using the Aura/MLS and TIMED/SABER satellite data, ERA5 reanalysis and the Extended-Reconstructed Sea Surface Temperature and Optimally-Interpolated sea ice concentration data sets. We find a significant anti-correlation between the QQO and the meridional wind at 86 km altitude measured by a medium frequency spaced antenna radar at Davis. The QQO signal is also correlated with vertical transport as determined from evaluation of carbon monoxide (CO) concentrations in the mesosphere. Together this relationship suggesting that a substantial part of the QQO is the result of adiabatic heating and cooling driven by the meridional flow. The presence of quasi-stationary or persistent patterns in the ERA5 data geopotential anomaly and the meridional wind anomaly data during warm and cold phases of the QQO suggests a tidal or planetary wave influence in its formation, which may act on the filtering of gravity waves to drive an adiabatic response in the mesosphere. The QQO signal potentially arises from an ocean-atmosphere response, and appears to have a signature in Antarctic sea ice extent.